Single production of an exotic bottom partner at LHC - Alvarez, Ezequiel (2014)
We study single production and detection at the LHC run II of exotic partners of the bottom quark. For masses larger than 1 TeV single production can dominate over pair production that is suppressed due to phase space. The presence of exotic partners of the bottom is motivated in models aiming to solve the AFB b anomaly measured at LEP and SLC. Minimal models of this type with partial compositeness predict, as the lightest bottom partner, a new fermion V of electric charge -4/3, also called mirror. The relevant coupling for our study is a WVb vertex, which yields a signal that corresponds to a hard W, a hard b-jet and a forward light jet. We design a search strategy for the leptonic decay of the W, which avoids the large QCD multijet background and its large uncertainties. We find that the main backgrounds are W+ jets and tt̄, and the key variables to enhance the signal over them are a hard b-jet and the rapidity of the light jet. We determine the discovery reach for the LHC run II, in particular we predict that, for couplings of order ∼ g/10, this signal could be detected at a 95% confidence level with a mass up to 2.4TeV using the first 100 fb-1. © The Authors.